Active and passive defects in tetragonal tungsten bronze relaxor ferroelectrics. (5th October 2022) - Wang, Bi-Xia; Krogstad, M J; Zheng, H; Osborn, R; Rosenkranz, S; Phelan, D
Abstract: Tetragonal tungsten bronze (TTB) based oxides constitute a large family of dielectric materials which are known to exhibit complex distortions producing incommensurately modulated superstructures as well as significant local deviations from their average symmetry. The local deviations produce diffuse scattering in diffraction experiments. The structure as well as the charge dynamics of these materials are anticipated to be sensitive to defects, such as cation or oxygen vacancies. In this work, in an effort to understand how the structural and charge dynamical properties respond to these two types of vacancy defects, we have performed measurements of dielectric susceptibilities and single crystal diffraction experiments of two types of TTB materials with both 'filled' (Ba2 NdFeNb4 O15 and Ba2 PrFeNb4 O15 ) and 'unfilled' (Sr0.5 Ba0.5 Nb2 O6 ) cation sublattices. We also perform these measurements before and after oxygen annealing, which alters the oxygen vacancy concentrations. Surprisingly, we find that many of the diffuse scattering features that are present in the unfilled structure are also present in the filled structure, suggesting that the random fields and disorder that are characteristic of the unfilled structure are not responsible for many of the local structural features that are reflected in the diffuse scattering. Oxygen annealing clearly affected both color and dielectric properties, consistent with a diminishment of the oxygen vacancy concentration, but had little effect on observed diffuse patterns.